Soil-root interaction and effect on slope stabilization - Farshchi, Iman (2009)
The use of vegetation for preventing and controlling erosion for slope stabilization has being practiced throughout the world. This disciplines has recently gained a global recognition and was given a new entity “Ecological Engineering” defined as the design of sustainable ecosystem that integrate human society with its natural environment for the benefit of both. This soft approach of stabilizing slope confers numerous advantages, including high biodiversity, low maintenance, self-sustainability as well as being environmental-friendly. There are various conventional methods used to improve stability of slope, they all have merit and demerit, but the use of vegetation has other advantages as mentioned above plus root do not corrode, they are self-repairing, regenerating and adaptive. This gives the motivation to carry out this research; so as to gain more understanding on its soil-root interaction and effects on slope stabilization. The mechanical and hydrological effect of vegetation would be combined and their overall effect on slope stability stabilization and analyses would be evaluated.